Terapias mucogengivais na saúde periimplantar - Antonio, Amanda Vanzo [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Contemporary implantology aims to provide full rehabilitation for the patient, in which besides osseointegration, an absolute state of health, function and aesthetics shall be reached, almost always related to the quality of the soft peri-implant tissues. This way, the present study has the objective to describe techniques to increase the volume of keratinized tissue, for maintenance of health and longevity of osseointegrated titanium implants. Were reported two cases, from which, the first, by the clinical examination, a keratinized tissue deficiency was observed in the functional element 11, as well as initial exposure of the neck of the implant and, for correction of this case, was described a technique of a subepithelial connective tissue graft combined with laterally positioned flap. In the second case, the intervention for increase of keratinized tissue in posterior mandible was planned to be a free gingival graft (FGG) by the moment of uncovering procedure. Postoperatively, at the aesthetic region was observed both keratinized tissue gain, in width and cover of the exposed surface of the implant, however, more evident in later periods due to the creeping attachment. In the second case, after the repair process was observed that the FGG was capable to provide great increase of keratinized tissue at the peri-implant area. It can be concluded that both techniques were capable to increase the volume of peri-implant keratinized mucosa and, therefore, to keep health and greater predictability of the rehabilitations with osseointegrated titanium implants

A implantodontia atual visa proporcionar ao paciente uma reabilitação, na qual além da osseintegração, seja alcançado um estado adequado de saúde, função e estética, quase sempre relacionado com a qualidade do tecido mole periimplantar. Dessa forma, o presente estudo tem como objetivo a descrição de técnicas de aumento de volume de tecido queratinizado visando manutenção da saúde e longevidade de implantes de titânio osseointegrados. Para isso foram relatados dois casos clínicos, sendo que no primeiro, ao exame clínico foi observada deficiência de tecido queratinizado periimplantar no elemento 11 já em função, bem como início de exposição do pescoço do implante, e, para solução do mesmo, foi descrita uma técnica de enxerto de tecido conjuntivo subepitelial associado ao deslocamento lateral do retalho. No segundo caso, a intervenção para aumento de tecido queratinizado na região posterior de mandíbula foi planejada com enxerto gengival livre (EGL) no momento da reabertura dos implantes. No pós operatório do caso envolvendo área estética, foi observado tanto ganho de tecido queratinizado em espessura quanto recobrimento da porção exposta do implante, contudo, com maior evidência nos períodos mais tardios, em decorrência do creeping attachment. No segundo caso, após o período de reparo foi observado que o EGL foi capaz de promover grande ganho de tecido queratinizado na região periimplantar. Conclui-se, portanto, que ambas técnicas foram capazes de promover aumento no volume de mucosa queratinizada periimplantar e, consequentemente, manter saúde e maior previsibilidade de longevidade das reabilitações envolvendo implantes de titânio osseointegrados
Keywords: Implantes dentários; Tecido conjuntivo; Cirurgia bucal; Dental implants